Influência hidrodinâmica no balanço sedimentar: estudo de caso das praias estuarinas na ilha de Cotijuba - LOBO, Fabrício Costa (2019)
The Amazon Coastal Zone (ZCA) is modeled by the equilibrium of the erosive or depositional processes that can be caused by the action of waves, tides and coastal currents. Few studies of evolutionary models of beaches in the ZCA were carried out, most of them being on oceanic beaches. This makes the estuarine beaches still little known, even though they are important, complex and strongly impacted by the disordered growth and anthropic activities. The estuary Rio Pará has a great extension, main forcing by the currents of macro and mesomaré, the fluvial discharge coming from its tributaries, mainly of the river Tocantins, and the waves formed by local winds. Within this estuary, the island of Cotijuba is shaped by these physical agents that vary their intensity seasonally. Thus, the objective of this work is to evaluate the sedimentary balance of the estuarine fluvial beaches of the island of Cotijuba from the morphodynamic analysis and its relation with the currents of tide and waves. For this, surveys, sediment collection along sediments, sediment balance with sediment traps and physical data acquisition were carried out on three beaches: Pedra Branca, Vai-quem-quer and Flexeira, during the two Amazonian seasonal periods, in tide of New Moon springs tide. The beaches have greater sedimentary transport by action or influence of the waves, generated by the wind, but also receive impulse of the current of tide flood due to the orientation of the line of coast of the north portion of the island. Thus the morphology changes according to the seasonality, due to the predominant erosional aspect.